PERENCANAAN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) INDUSTRI TAHU DI KELURAHAN LOKTABAT UTARA, KALIMANTAN SELATAN - Yuniar, Villa; Noor, Rijali; Khair, Riza Miftahul; Abdi, Chairul (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Tofu is a soy-based culinary product. During the manufacturing process, the tofu industry generates solid refuse and liquid waste. The majority of the tofu industry lacks a sewage treatment infrastructure, so the resulting waste is discharged directly into the river. High levels of organic pollutants are present in liquid waste, which can cause significant pollution. The effluents discharged into the water must meet the established quality requirements. If the water discharged does not meet quality standards, it will pollute the environment. This research aims to evaluate the quality of wastewater produced by the tofu industry, as well as determine the most suitable treatment technology for the waste conditions and design a wastewater treatment plant (WWTP). The tofu industry's liquid effluent contains 2666.5 mg/L BOD, 12476.1 mg/L COD, and 3220.3 mg/L TSS. The selection of WWTP technology utilizes a scoring method based on criteria provided by the Technical Team for Sanitation Development. The chosen treatment unit is an Anaerobic-Aerobic Biofilter with a score of 4.3. The design of the WWTP model includes an equalization tank, initial sedimentation tank, anaerobic biofilter tank, aerobic biofilter tank, and final sedimentation tank.